Amycolatopsis thailandensis sp. nov., a poly(L-lactic acid)-degrading actinomycete, isolated from soil - Atchareeya Chomchoei (2018)
A novel actinomycete that was capable of degrading poly(L-lactic acid), strain CMU-PLA07T, was isolated from soil in northern Thailand. Strain CMU-PLA07T had biochemical, chemotaxonomic, morphological and physiological properties that were consistent with its classification in the genus Amycolatopsis. 16S rRNA gene sequence analysis showed that the isolate formed a phyletic line within the genus Amycolatopsis. Strain CMU-PLA07T was most similar to Amycolatopsis coloradensis IMSNU 22096T (99.5% 16S rRNA gene sequence similarity) and Amycolatopsis alba DSM 44262T (99.4%). However, strain CMU-PLA07T was distinguishable from the type strains of species of the genus Amycolatopsis on the basis of DNA-DNA relatedness and phenotypic data. Therefore, strain CMU-PLA07T is considered to represent a novel species of the genus Amycolatopsis, for which the name Amycolatopsis thailandensis sp. nov. is proposed. The type strain is CMU-PLA07T (=5JCM 16380T=BCC 38279T). © 2011 IUMS.